Novel Reconfigurable Filtering Rat-Race Coupler, Branch-Line Coupler, and Multiorder Bandpass Filter With Frequency, Bandwidth, and Power Division Ratio Control - Zhu, Xu; Yang, Tao; Chi, Pei-Ling; Xu, Ruimin (IEEE transactions on microwave theory and techniques, 2020)
In this article, for the first time, a novel four-port coupler with reconfigurable multifunctions of filtering rat-race coupler (FRC), filtering branch-line coupler (FBC), and conventional single-ended two-port multipole bandpass filter (BPF) is proposed. It simply consists of four varactor-loaded stepped-impedance resonators that are arranged symmetrically. Through appropriate coupling-type (electrical coupling or magnetic coupling) conversion, 90° or -90° phase shift between the adjacent resonators can easily be obtained and works as a key factor in the transformation between different filtering coupler modes. With this simple configuration, the proposed coupler achieves reconfigurable FRC and FBC with not only operating frequency tuning over a wide tuning range but also bandwidth and power division ratios (PDRs) control for each filtering mode. In addition, by imposing open circuit at any two ports, the four-port coupler can be converted to the conventional single-ended two-port BPFs with reconfigurable filter orders of second, third, and fourth. The measured results show that the FRC and FBC can continuously cover the frequency ranges of 1.21-1.67 and 1.2-1.61 GHz with -1-dB bandwidth tuning of 60-120 and 55-110 MHz, respectively. The 3- and 6-dB PDRs have been demonstrated for both filtering coupler modes. In single-ended two-port BPF mode, the frequency tuning ranges are measured of 1.12-1.6, 1.16-1.6, and 1.2-1.61 GHz, respectively, for the proposed two-port second-, third-, and fourth-order BPFs. Measured and simulated results are in good agreement, validating the proposed design method.